Взаимодействие компонентов адсорбента с металлами катализаторной сетки - Гринь, Григорий Иванович; Хильченко, Г. С.; Трофименко, Д. А.; Дейнека, Дмитрий Николаевич; Авина, Светлана Ивановна (Молодий вчений, 2019)
Проанализированы взаимодействия компонентов адсорбента с металлами каталитической сетки. Исследованный термодинамический анализ взаимодействия оксидов кальция и магния с соединениями платины, палладия и родия. Показано, что при взаимодействии с оксидами платины, с оксидами щелочноземельных металлов, наиболее вероятно образование 2MgO PtO₂, 4CaO PtO₂, 4BaO 4PtO₂. Установлено, что адсорбент на основе оксида Ca и Mg улавливает твердые частицы и газообразные оксиды платины с образованием 2MgO 2PtO₂, 4CaO 4PtO₂. Установлено возможность использования адсорбента для улавливании не только оксидов платины и палладия, но и оксида родия. В работе выбран алгоритм расчета и предложены методики для определения стандартных термодинамических характеристик сложных оксидных соединений кальция и магния с благородными металлами. Проведенные исследования позволили установить эффективность использования оксидных щелочноземельных металлов и наметить дальнейшие пути проведения исследований.

The world level of use of platinum metals increases every year, and the average increase in their production decreases. Platinum, palladium and rhodium are widely used in various industries, including chemical, as catalysts for technological processes. Creating a new adsorbent will reduce the irretrievable loss of the catalyst in the production of nitric acid, simplify their further processing and return to the production process cycle. Co-operating of components of adsorbent is analysed with the metals of catalytic net. Investigational thermodynamics analysis of cooperation of oxides of calcium and magnesium with connections of platinum, palladium and rhodium. It is shown that at co-operating with the oxides of platinum, with the oxides of щелочноземельных metals, education is most credible 2MgO • PtO₂, 4CaO • PtO₂, 4BaO • 4PtO₂. It is set that an adsorbent on the basis of oxide of Ca and Mg catches particulate matters and gaseous oxides of platinum with education 2MgO • 2PtO₂, 4CaO • 4PtO₂. Possibility of the use of adsorbent is set for catching of not only oxides of platinum and palladium but also oxide of rhodium. The algorithm of calculation is inprocess chosen and methodologies of determination of standard thermodynamics descriptions of difficult oxide connections of calcium and magnesium offer with noble metals. For capturing platinoids lost by catalyst nets in the production of nitric acid, the use of adsorbents based on oxides of alkaline earth metals, which allow the capture of lost particles not only mechanically, but also due to the chemical binding of platinoids to complex stable compounds, is most appropriate. Thus, further research should be directed to the development of technology for the preparation of an adsorbent based on oxides of alkaline earth metals. The conducted studies allowed to establish the effectiveness of the use of oxide alkaline earth metals and outline further ways to conduct research.
Interaction of adsorbent components with catalyst net metal metals
Keywords: родий; палладий; платина; термодинамика; rhodium; palladium; platinum; catalyst grid; thermodynamics